Indoor Air Quality in UNIMAS Detar Putra Convocation Hall - Christopher J., Boniface; Mohammad Shahril, B. Osman; Syed Tarmizi, Syed Shazalic (ENCON 2013, 2013)
This study was conducted to determine the comfort conditions and Indoor Air Quality during convocation in UNIMAS convocation hall, Sarawak Malaysia with the capacity of 5000 occupants. Heating, ventilating and air conditioning (HVAC) systems of the hall should be design to serve and providing good indoor air quality. For the investigations, all of the IAQ monitoring equipments used in this study were supplied and assisted from Department Of Occupational Safety and Health (DOSH) Ministry of Human Resources Malaysia. Monitoring equipments were used to obtain the IAQ data parameters were based on Industry Code Of Practice On Indoor Air Quality 2010 DOSH Malaysia. In this study, maximum and minimum air movement for convocation hall are 0.05 m/s and 0.09 m/s respectively below range and humidity of above 70% as specified by DOSH Malaysia. Approximately at 2500 occupant, carbon dioxide concentrations are between minimum 834 ppm and 890 ppm maximum. With these figures are indications of inadequate ventilation on UNIMAS Detar Putra Convocation hall.